2015
DOI: 10.4028/www.scientific.net/amm.752-753.485
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural and Mechanical Properties of Selective Laser Melted Al 4047

Abstract: Selective laser melting (SLM) has been recognized as a pertinent process for manufacturing of complex geometries. Al 4047 has been manufactured in this study with different processing parameters of the SLM process to obtain the optimal parameters suitable for required applications, as well as to determine the effect of these parameters and post-processing heat treatment on mechanical properties. A unique Al-Si eutectic microstructure is obtained with Al dendrites growing in the scanning direction. Mechanical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 8 publications
1
4
0
1
Order By: Relevance
“…These studies have reported quasistatic tensile strength of SLM manufactured Ti-6Al-4V as comparable, and in cases better, to those of conventionally manufactured alloy [6,8]. Similar behavior has been observed for Al alloys AlSi10Mg [9] and AlSi12 [10,11]. Fatigue performance of the as-built alloys is usually impaired due to surface roughness as well as process-induced porosity.…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…These studies have reported quasistatic tensile strength of SLM manufactured Ti-6Al-4V as comparable, and in cases better, to those of conventionally manufactured alloy [6,8]. Similar behavior has been observed for Al alloys AlSi10Mg [9] and AlSi12 [10,11]. Fatigue performance of the as-built alloys is usually impaired due to surface roughness as well as process-induced porosity.…”
Section: Introductionsupporting
confidence: 67%
“…The specimens were melted using laser power of 350 W, and a scan speed of 930 mm/s (batch I). The details of the process set up can be seen elsewhere [10]. The specimens ( Fig.…”
Section: Experimental Methodologymentioning
confidence: 99%
“…Cylindrical samples were manufactured in a building direction perpendicular to the platform with dimensions of £ 9 Â 110 mm. Complete details of the process set up can be found in [26]. SLM processing was carried out with a laser power of 350 W, scan speed of 930 mm/s, hatch spacing of 0.19 mm and layer thickness of 50 lm, resulting in an energy density of 39.6 J/mm 3 .…”
Section: Experimental Methodologymentioning
confidence: 99%
“…Детали из сплава АК12 зачастую используют в качестве поршней двигателей, картеров двигателей автомобилей или автомобильных узлов [5][6][7][8][9]. На сегодняшний день уже исследованы изделия с использованием аддитивных технологий из сплава Al-12Si преимущественно в работах методом селективного лазерного плавления [8][9][10], но встречается и в работах с применением дуговой проволочной аддитивной технологией [11]. Из-за высокой отражательной способности лазера и из-за высокой пористости, получаемых дуговой аддитивной технологией изделий, стоит перейти к методу электронно-лучевого плавления.…”
Section: институт физики прочности и материаловедения со ран томскunclassified